Macht in de metropool Politieke elitevorming tijdens de demografische en economische bloeifase van Antwerpen (ca. 1400-1550) - Everaert, Janna (Amsterdam University Press, 2023)
During Antwerp's Golden Age, the city replaced Bruges as the primary trading hub of Western Europe. Antwerp transformed from a medium-sized Brabantine town to an unparalleled metropolis in the Low Countries with over 100.000 inhabitants. Although little is known regarding the impact of this transformation on the city's governance, Antwerp serves as an intriguing and exceptional case study. Unlike other trading metropolises such as sixteenth-century Lyon or seventeenth-century Amsterdam, where merchants increasingly occupied positions in the city council, this was not the case in Antwerp. This book 'Macht in de Metropool' reconstructs the compositions of Antwerp's city council between 1400 and 1550. It examines the profile of the different aldermen and mayors and how they evolved over time. Furthermore, the research analyses the real estate investments of this group and their relationship with key groups in society such as the merchants, the nobility, and the central administration.